(untitled) (Journal of Academic Research, 2020)
In the present study, describes the histochemical study of alimentary tract of Serranus scriba and Sarpa salpa using binuclear and light microscope. For this study, each 10 specimens for Morphological and histological examination were collected from Misurata coast, 2017. Periodic Acid Schiff’s (PAS) staining methods were applied to detect the different types of the mucous contents of the gastro-intestinal tract. The folded esophagus mucosa had stratified epithelium with mucous secreting goblet cells, which stained positive with PAS. The stomach of fishes consists of two parts (cardiac and pyloric). The mucosa of stomach of both types of fish, the pyloric caeci and small intestine were reacted positively to PAS.